Ternary positive electrode material encapsulated by metal organic framework and coated with polyoxometallate and preparation method of ternary positive electrode material
By using a polyoxylate coating with a metal organic frame encapsulated on the ternary positive electrode material, the lithium ion transmission restriction problem caused by the formation of electrolyte film in solid-state batteries is solved, and the effect of improving the performance of all-solid-state batteries and extending the cycle life is achieved.
Patent Information
- Application Number
- CN202510147321.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-11
AI Technical Summary
In a solid-state battery system, during charging and discharging, the solid electrolyte reacts with the positive electrode material to form an electrolyte membrane, limiting the transmission of lithium ions, resulting in reduced energy density and attenuation.
The polymetallic acid salt-encapsulated with a metal organic frame is used to coat the ternary positive electrode material. By introducing the polymetallic acid active material cladding layer encapsulated with a metal organic frame, the electrode electrolyte interface is improved and the performance of all solid-state batteries is improved.
It effectively solves the problem of poor stability during the cycle of uncovered ternary materials, improves the interface performance of the electrode electrolyte, extends the cycle life of the positive electrode material, and improves the specific capacity and charge and discharge performance of all solid-state batteries.
Smart Images

Figure CN119612613A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a ternary positive electrode material coated with polyoxometalate encapsulated by a metal organic framework and a preparation method thereof. Background Art
[0002] In recent years, high-energy-density lithium-ion batteries have been widely used in portable electronic devices and electric vehicles. However, organic electrolytes are usually used in lithium-ion batteries, so they are inevitably flammable and explosive during use. Replacing liquid electrolytes with solid electrolytes can not only improve safety, but also make it possible to use high-energy-density lithium metal negative electrodes. At present, since the solid-state battery system is mainly "solid-solid" contact, there are a series of interface problems during the charging and discharging process. One of the reasons is that during the charging and discharging process, the solid electrolyte reacts with the positive electrode material, and a layer of electrolyte film (CEI film) is formed on the surface of the positive electrode material, thereby limiting the transmission of lithium ions, and finally leading to a decrease and attenuation of energy density. In order to solve this problem, different types of coating materials have been reported one after another.
[0003] In the prior art, common coating materials include carbon materials, oxides and sulfides, etc. These materials are coated on the surface of the electrode material by physical or chemical methods. For example: In 2023, Huading Guolian Battery Materials Co., Ltd. disclosed a ternary positive electrode material and its preparation method, and a lithium-ion battery (CN117410469A). The ternary positive electrode material of this invention can enhance the conductivity of electrons, improve the slurry efficiency, reduce the internal resistance of lithium-ion batteries, and improve the performance and cycle stability of lithium-ion batteries. Its main applicable field is liquid batteries. Due to the use of liquid phase preparation method, it may have an important impact on the application performance in the field of solid-state batteries. Furthermore, the simple carbon coating has limited improvement in the electrochemical performance of some electrode materials.
[0004] In addition, oxide coating is considered to be another effective coating method. For example, in 2024, GEM (Wuxi) Energy Materials Co., Ltd. disclosed a high-entropy oxide solid-state coated positive electrode material and its preparation method and application (CN118545773A). This coating method mainly solves the structural damage caused by lithium removal on the surface of the positive electrode material particles, thereby achieving a significant improvement in the electrochemical performance of the ternary positive electrode material. However, it often faces the problem of insufficient adhesion and insufficient conductivity between the coating layer and the substrate. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a metal organic framework encapsulated polyoxometalate coated ternary positive electrode material and a preparation method thereof. The present invention solves the problem of poor stability of uncoated ternary materials during the cycle by introducing a metal organic framework encapsulated polyoxometalate active material coating layer, and realizes / achieves the purpose of improving the electrode electrolyte interface and improving the performance of all-solid-state batteries.
[0006] <First aspect> A method for preparing a ternary positive electrode material coated with a polyoxometalate encapsulated by a metal organic framework comprises the following steps: a), preparing a metal A salt solution; preparing an ammonium molybdate compound into an ammonium molybdate compound solution, heating the ammonium molybdate compound solution to boiling, adding the metal A salt solution dropwise, reacting at a constant temperature after the addition, filtering and recrystallizing to obtain an Anderson type polyoxometalate; Wherein, the metal A salt includes one of Fe2(SO4)3, Ni(NO3)2, CuSO4, Cr(NO3)3, and CoSO4; b), dissolving Anderson type polyoxometalate, metal B salt and organic ligand in water, reacting at a certain temperature to obtain polyoxometalate encapsulated by metal organic framework; in step b), metal B salt includes copper nitrate trihydrate; the organic ligand includes pyridine-4,5-dicarboxylic acid and / or 4,4'-bipyridine; c) mixing the positive electrode material and the metal organic framework encapsulated polyoxometalate prepared in step b) in proportion, and ball milling to obtain a ternary positive electrode material coated with the metal organic framework encapsulated polyoxometalate.
[0007] In step a), the molar ratio of metal A salt to ammonium molybdate compound is (2-4): (4-8); And / or, in step a), the constant temperature reaction conditions are: temperature of 70° C.-120° C., reaction time of 2 h-12 h; the number of recrystallizations is 2-6 times.
[0008] Step b) specifically comprises the following steps: A certain amount of Anderson-type polyoxometalate, copper nitrate trihydrate, pyridine-4,5-dicarboxylic acid, and 4,4'-bipyridine are dissolved in water, stirred at room temperature for a period of time, the pH value is adjusted to 2-6, and reacted at a certain temperature for a period of time to obtain a polyoxometalate encapsulated by a metal organic framework; wherein: The mass ratio of polyoxometalate to copper nitrate trihydrate is (1-10):1; The mass ratio of pyridine-4,5-dicarboxylic acid to polyoxometalate is 1:(2-20); The mass ratio of 4,4'-bipyridine to polyoxometalate is 1:(2-20); The volume of water is 50-500mL.
[0009] In step b), the reaction conditions are: reaction temperature 100-120° C.; reaction time 6-8 hours.
[0010] In step c), the positive electrode material includes at least one of NCM811, NCM111, and NCM622; the mass ratio of the polyoxometalate encapsulated by the metal organic framework to the positive electrode material is 0.1-0.2:1, the ball mill speed is 450-600rpm, and the ball milling time is 4-6 hours.
[0011] <Second Aspect> The metal organic framework encapsulated polyoxometalate coated ternary positive electrode material prepared by the preparation method as described above.
[0012] <Third Aspect> A method for preparing a composite positive electrode material comprises mixing the metal organic framework encapsulated polyoxometalate-coated ternary positive electrode material, a solid electrolyte, and conductive fibers, and ball milling to obtain the metal organic framework encapsulated polyoxometalate-coated composite positive electrode material.
[0013] The solid electrolyte includes Li6PS5Cl, Li3PS4, Li6PS7, Li 5.5 PS 4.5 Cl 1.5 At least one of; And / or, the mass ratio of metal organic framework encapsulated polyoxometalate coated ternary cathode material: solid electrolyte: conductive fiber purchased from Tianjin Jinglin New Materials Technology Co., Ltd. is (50-90):(15-35):(0.1-2).
[0014] <Fourth Aspect> The composite positive electrode material prepared by the preparation method as described above also falls within the protection scope of the present invention.
[0015] <Fifth Aspect> An all-solid-state battery comprises a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the composite ternary positive electrode material coated with polyoxometalate encapsulated by a metal organic framework as described above.
[0016] The negative electrode can include a lithium indium sheet.
[0017] The electrolyte includes a sulfide solid electrolyte.
[0018] The preparation method of the sulfide solid electrolyte comprises the following steps: Step 1, ball milling and mixing Li2S, P2S5 and LiCl; Step 2: calcining the mixed raw materials of step 1 to obtain a sulfide solid electrolyte.
[0019] In step 1, the ball-to-material ratio is (5-50):(1-10).
[0020] In step 1, the ball milling beads are zirconium oxide ball milling beads; the diameter of the ball milling beads is 1mm-10mm.
[0021] In step 1, a high-energy planetary ball mill is used for ball milling at a rotation speed of 100 r / min-900 r / min; and the ball milling time is 2h-16h.
[0022] In step 2, a muffle furnace is used for calcination at a temperature of 300°C to 800°C, a calcination time of 3h to 12h, and a heating rate of 0.1°C / min to 2°C / min.
[0023] Polyoxometalates (POMs) encapsulated in metal organic frameworks (MOFs); on the one hand, MOFs can provide a protective environment to reduce the degradation or aggregation of POMs during use, thereby enhancing the stability of the system. On the other hand, the pores of MOFs can be adjusted to optimize the distribution and reaction environment of POMs and improve their performance. POMs have good electrical conductivity and electrochemical stability and can be used as positive electrode materials for solid-state batteries. The synergistic effect of the two has the potential to be applied to the field of all-solid-state batteries.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. High specific capacity: The present invention found that the electrochemical activity of the ternary cathode material coated with polyoxometalates encapsulated by metal organic frameworks is much higher than that of the traditional single metal oxide cathode material, and its specific capacity can reach more than 200 mAh / g. The use of MOFs encapsulation can increase the specific surface area of POMs, increase the contact area of active substances and the location of electrochemical reactions, and thus further improve the specific capacity of POMOFs.
[0025] 2. Long cycle life: MOFs encapsulation can effectively protect the positive electrode material and extend its cycle life.
[0026] 3. Controllable embedding and release performance: The pore structure in MOFs matches the POMs crystal, thus achieving controllable embedding and release performance. This helps to improve the charge and discharge performance and capacity of the ternary cathode material encapsulated by the metal organic framework polyoxometalate. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 TEM spectrum of polyoxometalate-coated NCM811 encapsulated in a metal-organic framework; Figure 2 This is a 300-cycle charge-discharge cycle diagram of the full battery assembled with NCM811 coated with polyoxometalate encapsulated by the metal organic framework prepared in Example 1 at 1.0 C. DETAILED DESCRIPTION
[0028] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0029] The following embodiments and comparative examples: Conductive fiber: Tianjin Jinglin New Material Technology Co., Ltd. Example 1 1. Preparation of polyoxometalates 1.1. Weigh 2.4g Fe2(SO4)3, add 40ml deionized water, stir until dissolved, and obtain Fe2(SO4)3 solution; 1.2, 10.6 g (NH4)6Mo7O 24 ·4H2O was dissolved in 160mL water, heated to boiling, and the Fe2(SO4)3 solution prepared in step 1.1 was added dropwise under stirring. With the continuous addition of Fe2(SO4)3 solution, the solution gradually changed from colorless to dark red. The pH change was monitored in real time, and the pH of the solution was adjusted to 2.8 by hydrochloric acid. The reaction was kept at a constant temperature for 1 hour, and filtered while hot (80°C). After 12 hours, brown-red flaky crystals were precipitated from the filtrate. The filtrate was recrystallized three times in an 80°C water bath to obtain pure Fe-based polyoxometalate; 2. Preparation of polyoxometalates encapsulated in metal-organic frameworks Dissolve polyoxometalate (480 mg), copper nitrate trihydrate (150 mg), pyridine-4,5-dicarboxylic acid (59 mg), and 4,4'-bipyridine (57 mg) in deionized water (15 mL), stir at room temperature for 1 h, add 6 M HCl to reduce the pH of the mixed solution to 3.4, transfer it to a reactor, react at 120 ° C for 6 h, and obtain green block crystals.
[0030] 3. Metal-organic framework encapsulated polyoxometalate-coated NCM811 NCM811 and the metal organic framework encapsulated polyoxometalate prepared in step 2 were mixed by ball milling at a mass ratio of 1:0.1. The ball mill speed was 450 rpm and the ball milling time was 4 hours to obtain NCM811 coated with metal organic framework encapsulated polyoxometalate.
[0031] 4. Preparation of Li6PS5Cl solid electrolyte: Li2S, P2S5 and LiCl were used as raw materials and added into a zirconia ball mill at a ball-to-material ratio of 30:1 and mixed evenly. The mass ratio of Li2S, P2S5 and LiCl was 2.71:2.62:1. The sealed ball mill was then fixed on a high-energy planetary ball mill and ball milled at 500 rpm for 15 hours. The material was then scraped off the wall of the ball mill, and the obtained powder was pressed into a tablet and vacuum-sealed in a quartz tube and then placed in a muffle furnace and heated to 500°C at a rate of 0.5°C for calcination for 7 hours. After cooling to room temperature, the obtained material was ground to obtain a solid electrolyte (Li6PS5Cl) and bottled for later use.
[0032] 5. Preparation of NCM811 composite cathode material coated with polyoxometalate encapsulated by metal organic framework: The metal organic framework encapsulated polyoxometalate-coated NCM811 (350 mg) prepared in step 3, Li6PS5Cl (145 mg) prepared in step 4, and the conductive fiber (5 mg) purchased by Tianjin Jinglin New Materials Technology Co., Ltd. were weighed into a 25 mL zirconia ball mill according to a mass ratio of 70:29:1. The total mass of the material was 500 mg, the ball-to-material ratio was controlled to be 30:1, and the diameter of the zirconia ball milling beads used was 3 mm. Then the sealed ball milling jar was fixed on a high-energy planetary ball mill and ball milled at 500 r / min for 8 hours; the metal organic framework encapsulated polyoxometalate-coated NCM811 composite positive electrode material was obtained.
[0033] 6. Application performance testing Then, the all-solid-state battery was assembled using Li / In as the negative electrode and Li6PS5Cl solid electrolyte as the electrolyte layer, and the charge and discharge performance was tested.
[0034] Example 2 1. Preparation of polyoxometalates: Weigh 2.4g Fe2(SO4)3, add 40ml deionized water, stir until dissolved, and obtain Fe2(SO4)3 solution. 10.6g(NH4)6Mo7O 24·4H2O was dissolved in 160mL water, heated to boiling, and Fe2(SO4)3 solution was added dropwise under stirring. With the continuous addition of Fe2(SO4)3 solution, the solution gradually changed from colorless to dark red. The pH change was detected in real time, and the pH of the solution was adjusted to 2.8 by hydrochloric acid. The reaction was kept at a constant temperature for 1 hour, and filtered while hot. After 12 hours, brown-red flaky crystals were precipitated. Recrystallization was performed in a water bath at 80℃ for 3 times to obtain pure Fe-based polyoxometalate (10 g).
[0035] 2. Preparation of polyoxometalates encapsulated in metal-organic frameworks: Dissolve polyoxometalates (480 mg), copper nitrate trihydrate (150 mg), pyridine-4,5-dicarboxylic acid (59 mg), and 4,4'-bipyridine (57 mg) in deionized water (15 mL), stir at room temperature for 1 h, add 6 M HCl to reduce the pH of the mixed solution to 3.4, transfer it to a reactor, and react at 120 °C for 6 h to obtain green block crystals.
[0036] 3. Metal-organic framework encapsulated polyoxometalate-coated NCM111 NCM111 and the metal organic framework encapsulated polyoxometalate prepared in step 2 were mixed by ball milling at a mass ratio of 1:0.1. The ball mill speed was 450 rpm and the ball milling time was 4 hours to obtain metal organic framework encapsulated polyoxometalate coated NCM111.
[0037] 4. Preparation of Li6PS5Cl solid electrolyte: Take Li2S, P2S5 and LiCl as raw materials, add them into the zirconia ball mill at a ball-to-material ratio of 30:1 and mix them evenly. Then fix the sealed ball mill on a high-energy planetary ball mill and mill it at 500rpm for 15h. Then scrape the material from the wall of the ball mill, press the obtained powder into a tablet, vacuum seal it into a quartz tube, and place it in a muffle furnace and heat it to 500℃ at a rate of 0.5℃ for calcination for 7h. After cooling to room temperature, grind the obtained material to obtain a solid electrolyte (Li6PS5Cl), which is bottled for later use.
[0038] 5. Preparation of NCM111 composite cathode material coated with polyoxometalate encapsulated by metal organic framework: The metal organic framework encapsulated polyoxometalate-coated NCM111 (350 mg) prepared in step (3), Li6PS5Cl (145 mg) prepared in step (4), and the conductive fiber (5 mg) purchased from Tianjin Jinglin New Materials Technology Co., Ltd. were weighed into a 25 mL zirconia ball mill according to a mass ratio of 70:29:1. The total mass of the material was 500 mg, the ball-to-material ratio was controlled to be 30:1, and the diameter of the zirconia ball milling beads used was 3 mm. Then the sealed ball milling jar was fixed on a high-energy planetary ball mill and ball milled at 500 r / min for 8 hours; the metal organic framework encapsulated polyoxometalate-coated NCM111 composite positive electrode material was obtained.
[0039] 6. Application performance testing Then, the all-solid-state battery was assembled using Li / In as the negative electrode and Li6PS5Cl solid electrolyte as the electrolyte layer, and the charge and discharge performance was tested.
[0040] Example 3 1. Preparation of polyoxometalates: Weigh 2.4g Fe2(SO4)3, add 40ml deionized water, stir until dissolved, and obtain Fe2(SO4)3 solution. 10.6g(NH4)6Mo7O 24 ·4H2O was dissolved in 160mL water, heated to boiling, and Fe2(SO4)3 solution was added dropwise under stirring. With the continuous addition of Fe2(SO4)3 solution, the solution gradually changed from colorless to dark red. The pH change was detected in real time, and the pH of the solution was adjusted to 2.8 by hydrochloric acid. The reaction was kept at a constant temperature for 1 hour, and filtered while hot. After 12 hours, brown-red flaky crystals were precipitated. Recrystallization was performed in a water bath at 80℃ for 3 times to obtain pure Fe-based polyoxometalate (10 g).
[0041] 2. Preparation of polyoxometalates encapsulated in metal-organic frameworks: Dissolve polyoxometalates (480 mg), copper nitrate trihydrate (150 mg), pyridine-4,5-dicarboxylic acid (59 mg), and 4,4'-bipyridine (57 mg) in deionized water (15 mL), stir at room temperature for 1 h, add 6 M HCl to reduce the pH of the mixed solution to 3.4, transfer it to a reactor, and react at 120 °C for 6 h to obtain green block crystals.
[0042] 3. Metal-organic framework encapsulated polyoxometalate-coated NCM622 NCM622 and the metal organic framework encapsulated polyoxometalate prepared in step 2 were mixed by ball milling at a mass ratio of 1:0.1. The ball mill speed was 450 rpm and the ball milling time was 4 hours to obtain metal organic framework encapsulated polyoxometalate coated NCM622.
[0043] 4. Preparation of Li6PS5Cl solid electrolyte: Take Li2S, P2S5 and LiCl as raw materials, add them into the zirconia ball mill at a ball-to-material ratio of 30:1 and mix them evenly. Then fix the sealed ball mill on a high-energy planetary ball mill and mill it at 500rpm for 15h. Then scrape the material from the wall of the ball mill, press the obtained powder into a tablet, vacuum seal it into a quartz tube, and place it in a muffle furnace and heat it to 500℃ at a rate of 0.5℃ for calcination for 7h. After cooling to room temperature, grind the obtained material to obtain a solid electrolyte (Li6PS5Cl), which is bottled for later use.
[0044] 5. Preparation of NCM622 composite cathode material coated with polyoxometalate encapsulated by metal organic framework: The metal organic framework encapsulated polyoxometalate-coated NCM622 (350 mg) prepared in step (3), Li6PS5Cl (145 mg) prepared in step (4), and the conductive fiber (5 mg) purchased from Tianjin Jinglin New Materials Technology Co., Ltd. were weighed into a 25 mL zirconia ball mill according to a mass ratio of 70:29:1. The total mass of the material was 500 mg, the ball-to-material ratio was controlled to be 30:1, and the diameter of the zirconia ball milling beads used was 3 mm. Then the sealed ball milling jar was fixed on a high-energy planetary ball mill and ball milled at 500 r / min for 8 hours; the metal organic framework encapsulated polyoxometalate-coated NCM622 composite positive electrode material was obtained.
[0045] 6. Application performance testing Then, the all-solid-state battery was assembled using Li / In as the negative electrode and Li6PS5Cl solid electrolyte as the electrolyte layer, and the charge and discharge performance was tested.
[0046] Comparative Example 1 Comparative Example 1 is NCM811 without surface modification. The steps are basically the same as those in Example 1, except that the surface of NCM811 is not treated.
[0047] Comparative Example 2 Comparative Example 2 is NCM622 without surface modification. The steps are basically the same as those in Example 2, except that the surface of NCM622 is not treated.
[0048] Comparative Example 3 Comparative Example 3 is NCM111 without surface modification. The steps are basically the same as those in Example 3, except that the surface of NCM111 is not treated.
[0049] Performance Testing The performance of the composite positive electrode materials coated with polyoxometalate encapsulated by the metal organic framework prepared in Examples 1-3 and the composite positive electrode materials prepared in Comparative Examples 1-3 were tested.
[0050] Assembly of all-solid-state battery: Weigh 100 mg of the prepared solid electrolyte (Li6PS5Cl) into a 10 mm stainless steel tableting mold, press the electrolyte sheet at a pressure of 180 MPa, then add 10 mg of positive electrode material (the composite positive electrode material coated with polyoxometalate encapsulated by the metal organic framework prepared in Example 1-3 or the composite positive electrode material prepared in Comparative Example 1-3) on one side of the electrolyte, press it again at a pressure of 360 MPa, then demould it and load it into the solid-state battery test mold of Nobadi, then add a 9 mm lithium indium sheet (the thickness of the lithium sheet is 30 microns and the thickness of the indium sheet is 100 microns) on the other side of the electrolyte sheet, and finally load the Al sheet current collector on the positive electrode side and the Cu current collector on the negative electrode side to complete the packaging. Take out the battery test mold, put it into the battery fixture, and press it at a pressure of 50 MPa to obtain a sandwich-type all-solid-state battery. The assembled full battery is subjected to a capacitor discharge test. At room temperature, 0.1c charge and discharge, the discharge specific capacity after 100 cycles and the capacity retention rate after 100 cycles are tested. The results are shown in Table 1: Table 1
[0051] Figure 2 This is a 300-cycle charge-discharge cycle diagram of the full battery assembled with NCM811 coated with polyoxometalate encapsulated by the metal organic framework prepared in Example 1 at 1.0 C.
[0052] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a ternary positive electrode material coated with polyoxometalate encapsulated by a metal organic framework, characterized in that: The following steps are involved: a), preparing a metal A salt solution; preparing an ammonium molybdate compound into an ammonium molybdate compound solution, heating the ammonium molybdate compound solution to boiling, adding the metal A salt solution dropwise, reacting at a constant temperature after the addition, filtering and recrystallizing to obtain an Anderson type polyoxometalate; Wherein, the metal A salt includes one of Fe2(SO4)3, Ni(NO3)2, CuSO4, Cr(NO3)3, and CoSO4; b), dissolving Anderson type polyoxometalate, metal B salt and organic ligand in water, reacting at a certain temperature to obtain polyoxometalate encapsulated by metal organic framework; in step b), metal B salt includes copper nitrate trihydrate; the organic ligand includes pyridine-4,5-dicarboxylic acid and / or 4,4'-bipyridine; c) mixing the positive electrode material and the metal organic framework encapsulated polyoxometalate prepared in step b) in proportion, and ball milling to obtain a ternary positive electrode material coated with the metal organic framework encapsulated polyoxometalate.
2. The preparation method according to claim 1, characterized in that: In step a), the molar ratio of the metal A salt to the ammonium molybdate compound is (2-4): (4-8); And / or, in step a), the constant temperature reaction conditions are: temperature of 70° C.-120° C., reaction time of 2 h-12 h; the number of recrystallizations is 2-6 times.
3. The preparation method according to claim 1, characterized in that: Step b) specifically comprises the following steps: A certain amount of Anderson-type polyoxometalate, copper nitrate trihydrate, pyridine-4,5-dicarboxylic acid, and 4,4'-bipyridine are dissolved in water, stirred at room temperature for a period of time, the pH value is adjusted to 2-6, and reacted at a certain temperature for a period of time to obtain a polyoxometalate encapsulated by a metal organic framework; wherein: The mass ratio of polyoxometalate to copper nitrate trihydrate is (1-10):1; The mass ratio of pyridine-4,5-dicarboxylic acid to polyoxometalate is 1:(2-20); The mass ratio of 4,4'-bipyridine to polyoxometalate is 1:(2-20); The volume of water is 50-500mL.
4. The preparation method according to claim 1, characterized in that: In step b), the reaction conditions are: reaction temperature 100-120° C.; reaction time 6-8 hours.
5. The preparation method according to claim 1, characterized in that: In step c), the positive electrode material includes at least one of NCM811, NCM111, and NCM622; the mass ratio of the polyoxometalate encapsulated by the metal organic framework to the positive electrode material is 0.1-0.2:1, the ball mill speed is 450-600rpm, and the ball milling time is 4-6 hours.
6. A ternary positive electrode material coated with polyoxometalate encapsulated by a metal organic framework prepared by the preparation method according to any one of claims 1 to 5.
7. A method for preparing a composite positive electrode material, characterized in that: The metal organic framework encapsulated polyoxometalate-coated ternary positive electrode material prepared by the preparation method of any one of claims 1 to 6, a solid electrolyte, and a conductive fiber are mixed and ball milled to obtain a metal organic framework encapsulated polyoxometalate-coated composite positive electrode material.
8. The preparation method according to claim 7, characterized in that: The solid electrolyte includes Li6PS5Cl, Li3PS4, Li6PS7, Li 5.5 PS 4.5 Cl 1.5 At least one of; And / or, the mass ratio of the metal organic framework encapsulated polyoxometalate coated ternary positive electrode material: solid electrolyte: conductive fiber is (50-90):(15-35):(0.1-2).
9. A composite positive electrode material prepared by the preparation method according to claim 7 or 8.
10. An all-solid-state battery comprising a positive electrode, an electrolyte, and a negative electrode, wherein the positive electrode comprises the composite positive electrode material according to claim 9.
Citation Information
Patent Citations
Ternary positive electrode material, preparation method thereof and lithium ion battery
CN117410469A
High-entropy oxide solid-state coated positive electrode material as well as preparation method and application thereof
CN118545773A
Grinding preparation method and application of polyoxometallate-metal organic framework material
CN110444410A
Polypyrrole-coated polyacid-based metal organic framework composite material, negative electrode material, alkali metal ion battery and method
CN112421004A
Multi-oxide coated ternary lithium ion battery positive electrode material and preparation method thereof
CN112661205A
Cited By
Sodium-ion battery negative electrode material and preparation method and application thereof
CN120341269A
A sodium ion battery negative electrode material and its preparation method and application
CN120341269B